The Influence of Auditor Changes, Profitability, and Leverage on Audit Delay with Firm Size as a Moderating Variable - Khoirun Nisa', Aulia; Hidayat, Solikhul (Accounting Study Program, Faculty of Economics and Business, 2024)
This study aims to explore and analyze several factors that can affect audit delay, the impact of auditor changes on audit delay, the relationship between profitability and audit delay, the effect of leverage on audit delay, the role of company size in moderating the impact of auditor changes on audit delay, the effect of company size in strengthening the relationship between profitability and audit delay, and the ability of company size to moderate the effect of leverage on audit delay. In this study, company size is used as a moderating variable which is expected to influence the relationship between these factors and audit delay. The research population includes 43 food and beverage sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The findings of this study indicate that: auditor changes do not have a significant impact on audit delay, profitability also does not affect audit delay, while leverage is proven to have a significant positive effect on audit delay. In addition, company size does not strengthen the relationship between auditor turnover, profitability, and leverage in moderating their impact on audit delay.